Ответ:
х = +
х = -
Объяснение:
х ²-5х²+6=0
-4х²+6=0
-4х² = -6
х² = 6/4
х²= 3/2
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
х = +![\sqrt{\frac{3}{2} } \sqrt{\frac{3}{2} }](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7B3%7D%7B2%7D%20%7D)
х = -![\sqrt{\frac{3}{2} } \sqrt{\frac{3}{2} }](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7B3%7D%7B2%7D%20%7D)
Объяснение:
х ²-5х²+6=0
-4х²+6=0
-4х² = -6
х² = 6/4
х²= 3/2
х = +![\sqrt{\frac{3}{2} } \sqrt{\frac{3}{2} }](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7B3%7D%7B2%7D%20%7D)
х = -![\sqrt{\frac{3}{2} } \sqrt{\frac{3}{2} }](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7B3%7D%7B2%7D%20%7D)